Effects of nanosecond pulse electric fields on cellular elasticity. (May 2015) - Dutta, Diganta; Asmar, Anthony; Stacey, Michael
Highlights: NsPEFs induce differential cellular effects in the Young's modulus measured by AFM. Low and high nsPEF field strengths both significantly decrease membrane elasticity. High field strength nsPEFs effect both membrane and actin cytoskeleton. Abstract: We investigated the effects of a single 60 nanosecond pulsed electric field (nsPEF) of low (15 kV/cm) and high (60 kV/cm) field strengths on cellular morphology and membrane elasticity in Jurkat cells using fluorescent microscopy and atomic force microscopy (AFM). We performed force displacement measurements on cells using AFM and calculated the Young's modulus for membrane elasticity. Differential effects were observed depending upon pulsing conditions. We found that a single nsPEF of low field strength did not induce any apparent cytoskeletal breakdown and had minor morphological changes. Interestingly, force measurements and calculation of Young's modulus showed a significant decrease in membrane elasticity. A single nsPEF of high field strength induced stark morphological changes due to disruption of the actin cytoskeleton and a marked decrease in elasticity likely caused by irreversible membrane damage. We suggest that the cellular morphology is mainly dependent on stabilization by the actin cytoskeleton, while the elasticity changes are partially dependent on the cytoskeletal integrity.